Conocimientos, actitudes y hábitos de salud bucodental en trabajadores de Centros de Desarrollo Infantil Municipales de Riobamba, 2024. - Erazo Toledo, Monserrath Guillermina (2025)
The evaluation of the knowledge, attitudes and habits of workers at Child Development Centers shows the oral health perspective of the surveyed population and their educational discipline in preventive dentistry. The objective was to determine the knowledge, attitudes and oral health habits presented by workers at Child Development Centers in the city of Riobamba, 2024. The research was descriptive, cross-sectional, prospective, field, quantitative with a sample of 31 workers from Child Development Centers for which a questionnaire was applied using Microsoft Forms. The sociodemographic data of the population show an age between 26 and 59 years, without vulnerability, with a female predominance and a higher education level, knowledge of oral health that includes etiological factors, as well as prevention, show almost optimal levels in 87%; attitudes towards pain and bleeding show that 59% go to the dentist; habits such as frequent brushing and flossing, replacement of dental instruments, and regular dental visits are at 58%. It is concluded that the population has greater knowledge about etiological factors and oral health prevention. Although most maintain good hygiene habits, not all seek dental care when symptoms appear. Despite this awareness, oral symptoms are often underestimated, which could delay necessary professional care and compromise oral health. It is crucial to develop educational strategies that not only reinforce knowledge and preventive habits but also promote the importance of seeking dental care at the first sign of oral pathology